ANALISIS YURIDIS SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2023 TENTANG PETUNJUK BAGI HAKIM DALAM MENGADILI PERKARA PERMOHONAN PENCATATAN PERKAWINAN ANTAR-UMAT YANG BERBEDA AGAMA DAN KEPERCAYAAN TERHADAP PASAL 35 HURUF a UNDANG-UNDANG NOMOR 23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKAN - Simatupang, Gavrila Eleazar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The Supreme Court issued Supreme Court Circular Letter Number 2 of 2023 whichexplains the prohibition on judges throughout Indonesia from granting requests forregistration of interfaith marriages. Where this rule is in conflict with Article 35 Letter a ofLaw Number 23 of 2006. The issuance of SEMA resulted in a setback that hampered thedevelopment of the justice system in guaranteeing the rights of citizens from variousbackgrounds. It can be concluded that SEMA Number 2 of 2023 issued by the chairman ofthe Supreme Court has violated its constitutionality.The type of research used by the author is normative legal research or what is knownas "legal research". This means that this legal research aims to examine the conformity ofexisting norms regarding the prohibition on the practice of interfaith marriages in theSupreme Court Circular Letter Number 2 of 2023 with Article 35 Letter a of Law Number23 of 2006 concerning Population Administration using library study data collectiontechniques.SEMA No. 02 of 2023 is a legal instrument made by the Supreme Court which aimsto direct judges to reject applications for registering marriages between people of differentreligions. The urgency of SEMA was created based on pressure from several religiousorganizations in Indonesia who do not like marriages between people of different beliefs,whereas in Indonesia itself every citizen has the right to marry regardless of the religionadhered to by each partner. Any discrepancies between the Marriage Law and thePopulation Administration Law must be resolved through changes to the law, not throughSEMA. As well as the judge's freedom to decide fairly and in accordance with existingevidence. The issuance of SEMA seems to annul previously existing statutory regulations,in other words the Supreme Court does not review previously applicable statutoryregulations in making a decision. In practice, there are still district court judges who grantrequests for marriage registration. different religion.Keywords: SEMA, Population Administration Law, Marriage Law.